Study of factors affecting the productivity of nurses based on the ACHIEVE model and prioritizing them using analytic hierarchy process technique, 2012 - Payam Farhadi; Ramin Ravangard; Zahra Sajjadnia; Abdosaleh Jafari; Hajar Ghasemi; Iman Rahgoshay (Archives of Global Professionals, 2013)
Objective: Improving productivity is one of the most important strategies for social-economic development. Human resources are known as the most important resources in the organizations' survival and success. Aims: To determine the factors affecting the human resource productivity using the ACHIEVEa model from the nurses' perspective and then prioritize them from the perspective of head nurses using Analytic Hierarchy Process (AHP) technique. Settings and Design: Iran, Shiraz University of Medical Sciences teaching hospitals in 2012. Materials and Methods: This was an applied, cross-sectional and analytical-descriptive study conducted in two phases. In the first phase, to determine the factors affecting the human resource productivity from nurses' perspective, 110 nurses were selected using a two-stage cluster sampling method. Required data were collected using the Persian version of Hersey and Goldsmith's Human Resource Productivity Questionnaire. In the second phase, in order to prioritize the factors affecting human resource productivity based on the ACHIEVE model using AHP technique, pairwise comparisons matrices were given to the 19 randomly selected head nurses to express their opinions about those factors relative priorities or importance. Statistical Analysis Used: Collected data and matrices in two mentioned phases were analyzed using SPSS 15.0 and some statistical tests including Independent-Samples T-Test and Pearson Correlation coefficient, as well as, Super Decisions software (Latest Beta). Results: The human resource productivity had significant relationships with nurses' sex (P = 0.008), marital status (P < 0.001), education level (P < 0.001), and all questionnaire factors (P < 0.05). Nurses' productivity from their perspective was below average (44.97 ΁ 7.43). Also, the priorities of factors affecting the productivity of nurses based on the ACHIEVE model from the head nurses' perspective using AHP technique, from the highest priority to the lowest one, respectively, were: Clarity, Ability, Incentive, Evaluation, Help, Environment and Validity.Conclusions: According to the results and the priorities expressed by the head nurses in order to improve the productivity of nurses, providing the orientation, training and retraining courses for nurses, developing performance-based management systems and fair systems of reward and punishment, holding continuous performance evaluation and review meetings between individual nurses and their heads, increasing funding and improving organizational facilities, delegating authority to staff based on their abilities and capabilities, providing more welfare and recreational services and facilities such as nursery schools, transportation services, etc., for the nurses, esp. women nurses, are suggested.